Cost-effectiveness of preemptive pharmacological management of undesired effects in third molar extraction - Leonardo de Freitas Ferreira; Rênnis Oliveira da Silva; Edson Hilan Gomes de Lucena; Yuri Wanderley Cavalcanti (BrJP, 2024)
BACKGROUND AND OBJECTIVES: The extraction of third molars can lead to undesired effects such as pain, trismus, and edema, necessitating preemptive therapy to alleviate these effects. For this purpose, an economic evaluation was conducted to analyze the cost-effectiveness of preemptive drugs used in the extraction of third molars. METHODS: Costs were obtained from a market survey. Effectiveness measures were limitation of interincisal distance and postoperative pain, obtained from randomized clinical trials in the literature. For both models, a Monte Carlo simulation generated a hypothetical cohort of a thousand individuals, considering a 5% variation in estimates. The evaluated therapies were dexamethasone 8 mg (DX8); methylprednisolone 40 mg (MP); diclofenac 50 mg associated with tramadol 50 mg (DCTR); and dexamethasone 4mg associated with tramadol 50 mg (DXTR). RESULTS: MP and DCTR therapies were dominated in all scenarios. For the reduction of postoperative pain, DXTR treatment showed the best cost-benefit, with a net monetary benefit (NMB) gain of 31.10% compared to the lowest-cost treatment (DX, R$ 1.76). Considering the reduction in limitation of interincisal distance, DXTR medication presented higher cost-benefit compared to DX8 (NMB gain = 18.25%), being a preferred option alongside DX8. CONCLUSION: In the extraction of third molars, preemptive administration of dexamethasone 4mg associated with tramadol 50mg is the preferred cost-effective option to reduce postoperative pain and limitation of interincisal distance after 48 hours.